Analysis of Work Stress Diagnosis in Health Workers at Remaja HealthCenter in Samarinda City - Mirani Arizkha Uga; Iwan M Ramdan; Muhammad Sultan (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Community health centers are responsible for improving the quality of services and health development in their respective work areas. In this regard, healthcare professionals play a vital role in optimizing the quality of health services. Objective: This study aims to analyze the diagnosis of work stress among healthcare workers at Puskesmas Remaja, Samarinda City . Research Methods/ Implementation Methods : This quantitative study employed a cross-sectional design with a sample size of 32 individuals. Data was collected using the DASS 21 (Depression Anxiety Stress Scales-21) questionnaire. Univariate analysis was performed to describe the characteristics of respondents and the distribution of work stress in the form of frequency tables and percentages. Subsequently, bivariate analysis using the Chi-square test with a significance level of 5% (p<0.05) was conducted to examine the relationship between age, gender, marital status, and years of service with work stress among healthcare workers at Puskesmas Remaja, Samarinda City. Results : The results showed that 8 individuals (25%) fell into the category of work stress. Specifically, 4 individuals (12.5%) experienced mild stress, 3 (9.4%) moderate stress, and 1 person (3.1%) severe stress. Based on the analysis, marital status was the only variable found to have a significant relationship with the incidence of work stress among respondents (p=0.01). Conclusion/Lesson Learned : For future research, it is recommended to conduct similar studies with different designs, larger sample sizes, and include other variables to gain a more comprehensive understanding of the relationship between various factors and work stress among healthcare professionals.